Pengaruh Latihan Squat Thrust dan Throw Ball Medicine Terhadap Kemampuan Jauhnya Lemparan Chest Pass Bola Basket Ekstrakurikuler SMPN 22 Putri Hijau Bengkulu Utara - Nuraini Nuraini; Tono Sugihartono; Ari Sutisyana (SPORT GYMNASTICS : Jurnal Ilmiah Pendidikan Jasmani, 2020)
This study aims to determine the effect of Squat Thrust Training and Throw Ball Medicine on the Ability of the Throwing Basketball Chest Pass. This research was conducted on the basketball court of SMP Negeri 22 Putri Hijau North Bengkulu. in students who take basketball extracurricular. This study uses an experimental method, the design used is the design of one group pretest - posttest that is pretest before given treatment and posttest after being treated. The treatment given there are two forms of exercise namely Squat Thrust and Throw Ball Medicine. This design requires one group without comparison groups. The population in this study amounted to 25 students, sample selection using total sampling where the entire population was taken as a research sample. Data collection techniques in this study with the direct test method that is using the basketball throw test. Statistical prerequisite tests meet homogeneous requirements and normally distributed data based on statistical calculations obtained from the data t count = 8.803> t table = 2.064 with the level ? = 0.05. in the Test of the contribution of Squat Thrust and Throw ball medicine by 18.32% The results of this study indicate that there is an influence between squat thrust training and throw ball medicine on the ability of the extracurricular basketball chest throws of SMP Negeri 22 Putri Hijau North Bengkulu, so it can be concluded that Squat training Thrust and Throw Ball Medicine affect the distance of the chest pass and can be used as a training method to improve student achievement.